منهج الإمام ابن حبان في تعارض الرفع والوقف في كتابه "التقاسيم والأنواع": The Approach of Imam Ibn Hiban in the Contradictory of Rafa and Waqf in his Book of "Al- taqaseem Wal-anwaa". (Khairulummah, 2022)
This article discusses about the discrepancy between al- Rafa wal Wqaf, which is a most difficult, and intricate branch of Ilm -Ul- Ilal al Hadiths.Before Imam Hiban's time, more than fifty years, there was a contradictory on the reporting of the Hadith. Presumptions are the last arbitrator in the viewpoint of contemporary critics, who lack a conclusive conclusion in this issue. If the presumptions are favoring Rafa they consider it as Rafa, and if presumptions are favoring Wqaf it is taken as Wqaf. While the predecessors of ulamas in this field, in contrast, are like mathematical equations with their own standards for evaluating the chain of Hadith.  Even if there are many narrators for the Waqf Hadith, if the Rafa Hadith narrators are credible, they accept it. In this study I focus upon the question that, what is Imam Hiban's point of view in the book "Al-taqaseem Wal-anwaa"